WOMAN SOCIAL STRUGGLE IN ELLA WHEELER WILCOX’S ‘SOLITUDE’ - Mega Rosadi Nata; Eko Budi Setiawan (Universitas Katolik Widya Mandala Surabaya, 2020)
This research is about loneliness depict in Ella Wheeler Wilcox poem entitle Solitude. There aretwo purpose of this research, the first is to figure out speaker’s social struggle revealed bysituational irony in the poem, and second is to find out the imagery which illustrate the struggleof the speaker’s. The researcher used library research to analyze the analysis. The main data ofthis research taken from a poem entitled Solitude written by Ella Wheeler Wilcox in 1883. Sometheories used to analyze the data are theory of Irony, theory of Imagery and theory of WomanStruggle.